Teachers' Challenges in Improving Students' Collaboration Abilities - Mahlianurrahman,; Lasmawan, I Wayan; Candiasa, I Made; Suastra, I Wayan (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
This study identifies the challenges faced by teachers in the learning process at school, which have an impact on the low ability of student cooperation. The research data were obtained using interview techniques, observation and document studies. The collected data were analyzed by reducing data, presenting data, and drawing conclusions. The subjects in this study were elementary school teachers in East Kluet. The results showed that teachers had limited access to information, monotonous learning models, and lack of student involvement were the main factors in the low ability of student cooperation. In addition, the dominance of high-ability students and minimal opportunities for collaboration reduced important social interactions. The lack of integration of local wisdom and supporting facilities also contributed to this problem. These findings emphasize the need for innovation in learning models.